2004
DOI: 10.1038/sj.ijo.0802856
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoids in the physiopathology of excessive fat deposition and insulin resistance

Abstract: Glucocorticoids are important hormones in the regulation of metabolic homeostasis. We infused normal rats with dexamethasone given intracerebroventricularly (i.c.v.) for 3 days. This resulted in hyperphagia, hyperinsulinemia, and marked insulin resistance. Similar metabolic defects were observed following i.c.v. infusion of neuropeptide Y (NPY) in normal rats. As central dexamethasone infusion enhanced NPY content in the arcuate nucleus, it suggested that its metabolic effects are mediated by NPY. Moreover, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 97 publications
4
81
2
8
Order By: Relevance
“…This increase cannot be explained by the physiological understanding of resistin action derived from mice experiments, where a strong relationship between adiposity, insulin resistance and resistin was observed. 9,13,27 Similar to other human and rodent studies 4,7,28-31 our findings indicate that resistin levels were slightly higher in females than in males and decreased with age. Resistin concentrations were not significantly different between lean and overweight subjects.…”
Section: Discussionsupporting
confidence: 90%
“…This increase cannot be explained by the physiological understanding of resistin action derived from mice experiments, where a strong relationship between adiposity, insulin resistance and resistin was observed. 9,13,27 Similar to other human and rodent studies 4,7,28-31 our findings indicate that resistin levels were slightly higher in females than in males and decreased with age. Resistin concentrations were not significantly different between lean and overweight subjects.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of the group formation process on serum insulin followed that of the changes in body weight, as concentrations were significantly lower in subordinate compared with dominant females at week 7, regardless of SERT genotype. However, concentrations fell from baseline in l/l females but rose in s-variant females, indicating more studies are needed to determine whether social status-5HTTLPR differences in insulin secretion are due to differences in food intake or glucocorticoid-induced decreases in insulin sensitivity [72].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that obesity is associated with HPA axis dysregulation that may originate from increased forward drive, decreased sensitivity to negative feedback regulation, or altered sensitivity of peripheral tissues such as fat and skeletal muscle tissue to glucocorticoids [15,16]. Obese humans show a hypersensitive response to stimulation of the HPA axis, the magnitude of this exaggerated response being dependent on fat distribution [17,18].…”
Section: Obesity Is Associated With Dysregulation Of the Hpa Axismentioning
confidence: 99%